The possibilities and limitations of parental involvement in education: a survey of five schools on the East Rand - Schafer, Derek Linnihan (My University, 2014)
This study explores the nature and extent of past, present and future parental involvement in certain State [Model Cl schools. It researched the opinions and perceptions of parents, principals, teachers, and pupils of five East Rand English medium Secondary Schools in this regard and explored how socio-economic issues, issues around the professional status of teachers and practical and logistical considerations enhanced or hindered parental involvement in these schools. It further addressed the implications of increased or diminished parental involvement for school life in general, and pupil's academic achievements. The study found that the degree of parental involvement is contingent on the nature of the involvement, the parents' relationship with the professionals in a particular school, and various practical and logistical constraints that circumscribe the degree of parental involvement. It also found that parents are unlikely to interfere in the day-to-day organization of teaching and learning, and that if codes of conduct lay down guidelines for this participation, teachers need not fear that their professional status will be undermined by a greater degree of parental involvement. The study makes recommendations with regard to parental involvement, especially in the case of Black parents in Model C schools.